A slurry molding method of high-thickness aluminum nitride green body
Patent Information
- Application Number
- CN202511319478.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-16
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-09-16
AI Technical Summary
[0003]目前常规厚度的氮化铝陶瓷基板一般采用流延成型法制备,但流延的湿膜厚度过高,在干燥阶段易开裂,且制备常规厚度的氮化铝陶瓷基板的陶瓷浆料固含量过低,稳定性较差,难以满足高厚度氮化铝生坯成型需求
[0027] 1. Prepare ceramic powder by classifying and proportioning aluminum nitride powder according to its particle size. Select aluminum nitride powder with a D50 particle size of 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, and take coarse aluminum nitride powder with D50=3-5μm and fine aluminum nitride powder with D50=0.5-1.5μm in a mass ratio of (3-7):(3-7). Mix them evenly to obtain ceramic powder. Among them, by mixing coarse aluminum nitride powder and fine aluminum nitride powder with different particle sizes, a gradation effect is achieved, and the pores between large particles are filled with small particles, which further controls the stability, fluidity and solid content of ceramic slurry, which is beneficial to the preparation of ceramic substrates with high thickness, high density, high thermal conductivity and high mechanical properties.
Smart Images

Figure BDA0005598038600000201 
Figure BDA0005598038600000211
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic materials technology, specifically a method for preparing and molding high-thickness aluminum nitride green bodies. Background Technology
[0002] Aluminum nitride ceramic substrates have excellent thermal conductivity and are widely used in high-power light-emitting diodes and deep ultraviolet laser diodes as the core material for heat dissipation substrates of electronic devices. In order to meet the heat dissipation requirements of high-power electronic devices, the thermal capacity and mechanical properties of ceramic substrates are improved by increasing the substrate thickness.
[0003] Currently, aluminum nitride ceramic substrates of conventional thickness are generally prepared by tape casting. However, the wet film thickness of tape casting is too high, which makes it prone to cracking during the drying stage. In addition, the solid content of the ceramic slurry used to prepare aluminum nitride ceramic substrates of conventional thickness is too low, resulting in poor stability and making it difficult to meet the requirements for high-thickness aluminum nitride green body forming.
[0004] The isostatic pressing method is not only complicated, but also the high-thickness aluminum nitride green blanks prepared are prone to defects at the interface during sintering, resulting in poor sintering performance.
[0005] To address the aforementioned problems, this invention provides a method for preparing and molding high-thickness aluminum nitride green blanks. Summary of the Invention
[0006] The purpose of this invention is to provide a slurry forming method for high-thickness aluminum nitride green blanks, so as to solve the problems raised in the prior art.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] Step 1: Take aluminum nitride powder, sieve it to obtain coarse aluminum nitride powder and fine aluminum nitride powder; take coarse aluminum nitride powder and fine aluminum nitride powder, mix them evenly, and vacuum dry them to obtain ceramic powder;
[0009] Step 2: Add dispersant and surface modifier to organic solvent, mix well, add zirconia balls, and ball mill; add ceramic powder and sintering aid, ball mill; add adhesive, ball mill, to obtain ceramic slurry;
[0010] Step 3: Take the ceramic slurry, degas it under vacuum to obtain a vacuum-degassed ceramic slurry;
[0011] Step 4: Take the vacuum-degassed ceramic slurry, pass it through a casting machine, cast it, and dry it to obtain a ceramic green body;
[0012] Step 5: Take the ceramic green body, cut it, remove the glue, and obtain a glue-removing sheet; take the glue-removing sheet, introduce nitrogen gas, and sinter it to obtain a high-thickness ceramic substrate.
[0013] A more optimized method for preparing the adhesive solution is as follows: plasticizer and polyethylene glycol are added to an organic solvent and mixed evenly to obtain a mixed solvent; under the conditions of 65-75℃ and 1400-1600rpm, adhesive is slowly added to the mixed solvent and stirred thoroughly to obtain the adhesive solution.
[0014] More preferably, the plasticizer is one of dibutyl phthalate, triethyl citrate, and acetylated tributyl citrate; the binder is one of polyvinyl butyral and ethyl cellulose.
[0015] A more optimized method for preparing vacuum-degassed ceramic slurry is as follows: Take ceramic slurry and perform a first-stage vacuum degassed process under vacuum conditions of (-0.09)-(-0.07) MPa and ceramic slurry temperature of 40-45℃, controlling the viscosity of the ceramic slurry to 5900-6100 cP; increase the vacuum degree and perform a second-stage vacuum degassed process under vacuum conditions of (-0.1)-(-0.09) MPa and ceramic slurry temperature of 35-40℃, controlling the viscosity of the ceramic slurry to 10000-14000 cP, to obtain vacuum-degassed ceramic slurry.
[0016] A more optimized method for preparing ceramic green bodies is as follows: Vacuum-degassed ceramic slurry is passed through a casting machine, with the scraper height controlled at 2-2.2 mm and the casting conveyor speed at 0.1-0.3 m / min. The slurry passes through a heat preservation section, a constant speed section, a speed reduction section, a balance section, and a final drying section, each section being 1-2 m long. After drying, ceramic green bodies are obtained.
[0017] In a more optimized configuration, the doctor blade of the casting machine is a double-flat doctor blade; the film tape of the casting machine is a polyethylene terephthalate film tape with a silicone oil coating on its surface.
[0018] A more optimized ceramic green body thickness is 0.8-1.2 mm.
[0019] In a more optimized configuration, the temperature of the heat preservation section is set to 34-36℃; the temperature of the constant speed section is set to 39-41℃; the temperature of the deceleration section is set to 37-39℃; the temperature of the balancing section is set to 49-51℃; and the temperature of the final drying section is set to 64-66℃.
[0020] More optimized, the dispersant is one or more of polyethyleneimine and tartaric acid; the surface modifier is one of oleic acid and stearic acid; the organic solvent is one or more of methanol, anhydrous ethanol, isopropanol, ethyl acetate, and propyl acetate; the sintering aid is one or more of calcium fluoride and metallic aluminum powder; and the sphere diameter ratio of the zirconia spheres is: Φ5mm:Φ10mm:Φ15mm=(2-4):(4-6):(1-3).
[0021] The more optimized aluminum nitride powder has a D50 of 0.5-5 μm; the coarse aluminum nitride powder has a D50 of 3-5 μm; the fine aluminum nitride powder has a D50 of 0.5-1.5 μm; and the mass ratio of the coarse aluminum nitride powder to the fine aluminum nitride powder is (3-7):(3-7).
[0022] The optimized ceramic powder has a solid content of 99.90-99.99%, a D90 of 6-8 μm, and a specific surface area of 2.8-3.2 m². 2 / g.
[0023] In a more optimized version, in step five, the debinding process is as follows: under a heating rate of 0.5-1.5℃ / min, the temperature is raised to 460-560℃ and held for 90-120 minutes; the sintering process is as follows: under a heating rate of 0.5-2.5℃ / min, the temperature is raised to 1680-1780℃ and held for 3-6 hours.
[0024] A more optimized method for preparing aluminum nitride powder is as follows: Aluminum hydroxide is added to deionized water and mixed thoroughly to obtain an aluminum hydroxide solution; fructose is added to an ammonia solution and mixed thoroughly to obtain a fructose solution; urea is added to the aluminum hydroxide solution and mixed thoroughly; polyethylene glycol is added and mixed thoroughly to obtain a mixed solution; the mixed solution is slowly added to the fructose solution, and the reaction is carried out at 80-90℃ for 2-4 hours; the mixture is then filtered, washed, dried, pulverized, and sieved to obtain a precursor powder; the precursor powder is then vacuumed, nitrogen gas is introduced, and the reaction is carried out at 1550-1650℃ for 3-5 hours; finally, under an air atmosphere and at 600-700℃, decarburization is carried out for 2-4 hours to obtain aluminum nitride powder.
[0025] A more optimized ammonia solution concentration is 5-10%.
[0026] Compared with the prior art, the beneficial effects of the present invention are:
[0027] 1. Prepare ceramic powder by classifying and proportioning aluminum nitride powder according to its particle size. Select aluminum nitride powder with a D50 particle size of 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, and take coarse aluminum nitride powder with D50=3-5μm and fine aluminum nitride powder with D50=0.5-1.5μm in a mass ratio of (3-7):(3-7). Mix them evenly to obtain ceramic powder. Among them, by mixing coarse aluminum nitride powder and fine aluminum nitride powder with different particle sizes, a gradation effect is achieved, and the pores between large particles are filled with small particles, which further controls the stability, fluidity and solid content of ceramic slurry, which is beneficial to the preparation of ceramic substrates with high thickness, high density, high thermal conductivity and high mechanical properties.
[0028] 2. Perform staged vacuum degassing. In the first stage, under vacuum conditions of -0.09 to -0.08 MPa and ceramic slurry temperature of 40-45℃, vacuum degassing is performed to control the viscosity of the ceramic slurry to 6000-8000 cP. In this stage, a large amount of solvent is removed, and the viscosity and solid content of the slurry increase. This mainly removes large air bubbles in the lower viscosity slurry. In the second stage, under vacuum conditions of -0.095 to -0.09 MPa and ceramic slurry temperature of 35-40℃, vacuum degassing is performed to control the viscosity of the ceramic slurry to 10000-14000 cP. This stage mainly removes small air bubbles in the high viscosity slurry. By coordinating the above two stages of vacuum degassing, air bubbles in the slurry are eliminated to the maximum extent, resulting in a vacuum-degassed ceramic slurry, which is more conducive to the preparation of ceramic substrates with high thickness, high density, high thermal conductivity, and high mechanical properties.
[0029] 3. During the casting drying process, a double-plate doctor blade is used, with the blade height (including the height of the front and rear blades) controlled at 2-2.2 mm. Five-stage independent temperature-controlled drying is implemented, sequentially passing through a heat preservation stage, a constant-speed stage, a decreasing-speed stage, a balancing stage, and a final drying stage. The temperature in the heat preservation stage is set at 34-36℃ to maintain the stability of the slurry, promote the removal of low-boiling-point alcohol solvents, and form porous surface channels to provide pathways for subsequent solvent migration. The temperature in the constant-speed stage is set at 39-41℃, allowing the main solvent to migrate from the porous surface channels to the surface through capillary action, promoting the removal of the main solvent. The temperature in the decreasing-speed stage is set at... The drying process is initiated at 37-39℃ to reduce the drying rate, thereby decreasing the solvent removal rate, releasing internal stress, and preventing cracking of the aluminum nitride green body. The equilibrium section temperature is set at 49-51℃ to promote solvent diffusion from the high water content area to the low water content area through the temperature gradient, which dominates migration and promotes the removal of residual solvent. The final drying section temperature is set at 64-66℃ to ensure complete solvent removal. The hot air circulation system is then activated to prevent condensation backflow. The drying process balances the drying rate and the casting rate, avoiding both excessively fast drying to inhibit green body cracking and excessively slow drying to affect green body forming, which is beneficial to improving the thermal and mechanical properties of the ceramic substrate.
[0030] 4. Aluminum nitride powder is prepared using aluminum hydroxide as the aluminum source and fructose as the carbon source. A precursor powder is prepared by chemical precipitation, and the precursor powder is then used to prepare aluminum nitride powder by carbothermic reduction. In this process, aluminum hydroxide and fructose co-precipitate to form a co-precipitate of aluminum oxide and carbon, resulting in a highly dispersible precursor powder. Nitrogen gas is introduced, and the aluminum oxide, carbon, and nitrogen react to generate aluminum nitride. The prepared aluminum nitride powder has high dispersibility, high purity, small particle size, and narrow particle size distribution, making it easier to prepare ceramic substrates with high thickness, high density, high thermal conductivity, and high mechanical properties.
[0031] 5. Preparation of ceramic slurry: Polyethyleneimine and tartaric acid are selected as dispersants. The amino groups of polyethyleneimine are chemically bonded to the hydroxyl or alumino groups on the surface of aluminum nitride powder, forming a coating layer on the surface of aluminum nitride powder, which inhibits particle agglomeration through steric hindrance. Tartaric acid is added. On the one hand, the hydroxyl and carboxyl groups of tartaric acid are chemically bonded to the hydroxyl groups on the surface of aluminum nitride powder, forming a coating layer on the surface of aluminum nitride powder, which inhibits particle agglomeration through steric hindrance. On the other hand, the carboxyl groups of tartaric acid ionize to form carboxylate ions, which are adsorbed on the surface of aluminum nitride powder, inhibiting particle agglomeration through electrostatic interaction.
[0032] Polyethyleneimine is used as a dispersant. The molecular chain of polyethyleneimine is positively charged, which easily causes bridging flocculation. Tartaric acid is added. Tartaric acid is negatively charged, which neutralizes the positive charge of the polyethyleneimine molecular chain and avoids flocculation. The synergistic effect of the two improves the dispersibility of aluminum nitride powder, which is beneficial for preparing ceramic slurries with high solid content, further preparing high-thickness aluminum nitride green bodies, and making it easier to prepare ceramic substrates with high thickness, high density, high thermal conductivity and high mechanical properties.
[0033] Calcium fluoride and aluminum powder were selected as sintering aids. Calcium fluoride reacts with the alumina on the surface of aluminum nitride particles under high temperature conditions to generate a low-melting-point calcium aluminate liquid phase. The calcium aluminate liquid phase has excellent wettability and fills the gaps between aluminum nitride particles through capillary action, promoting particle rearrangement and pore removal, reducing the sintering temperature, and improving the density and thermal conductivity of the ceramic substrate. Aluminum powder is used as an aluminum source and reacts with nitrogen to form aluminum nitride crystal nuclei, which strengthens grain boundaries, purifies the aluminum nitride lattice, and refines the second phase, which is beneficial to improving the thermal and mechanical properties of the ceramic substrate.
[0034] Oleic acid was selected as a surface modifier for ceramic powder. Oleic acid has a hydrophilic carboxyl group and a hydrophobic alkyl long chain. The hydrophilic carboxyl group and the hydroxyl group or uncoordinated aluminum ion on the surface of aluminum nitride are chemically bonded to form a coating layer on the surface of aluminum nitride, which improves dispersibility and hydrolysis resistance, and makes it easier to prepare ceramic substrates with high thickness, high density, high thermal conductivity and high mechanical properties.
[0035] Anhydrous ethanol, isopropanol, and ethyl acetate were selected as organic solvents. Anhydrous ethanol and isopropanol were used as polar solvents. Hydroxyl groups reacted with polar groups on the powder surface to form hydrogen bonds, which enhanced the wettability of the powder, improved its dispersibility, and inhibited particle agglomeration. Ethyl acetate was used as a high-boiling-point solvent to regulate the evaporation rate and avoid cracking during the drying of high-thickness aluminum nitride green blanks. Detailed Implementation
[0036] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0037] The sources and types of substances involved in this invention are not particularly limited, and exemplary examples include:
[0038] Aluminum nitride powder, catalog number YM-ALN-W5, is supplied by Yumu (Ningbo) New Materials Co., Ltd.; polyethylene glycol, catalog number S30185-500g, is supplied by Shanghai Yuanye Biotechnology Co., Ltd.; dibutyl phthalate, catalog number S99072-500ml, is supplied by Shanghai Yuanye Biotechnology Co., Ltd.; polyvinyl butyral, catalog number CH0237, is supplied by Hubei Chenghai Chemical Co., Ltd.; zirconia spheres, catalog number 95 zirconium beads-01, are supplied by Shandong Hanhe New Materials Co., Ltd. The following products are provided by the company: Polyethyleneimine (item number E8420) from Beijing Solarbio Technology Co., Ltd.; Tartaric acid (item number Y54623-25g) from Shanghai Yuanye Biotechnology Co., Ltd.; Oleic acid (item number 112-80-1) from Chongqing Ruiya Biotechnology Co., Ltd.; Calcium fluoride (item number S50691-500g) from Shanghai Yuanye Biotechnology Co., Ltd.; and Aluminum powder (item number JZGR-202F) from Jinzhou Jinjiang Spraying Materials Co., Ltd.
[0039] Example 1:
[0040] Step 1: Preparation of ceramic slurry
[0041] S1: Select aluminum nitride powder with D50 = 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, take aluminum nitride coarse powder with D50 = 3μm and aluminum nitride fine powder with D50 = 0.5μm at a mass ratio of 3:7, mix them evenly, and vacuum dry them at a temperature of 115℃ for 3h to obtain ceramic powder;
[0042] S2: Take anhydrous ethanol, isopropanol, and ethyl acetate in a mass ratio of 1.5:1.5:0.5, mix them evenly to obtain an organic solvent; take 1g of dibutyl phthalate and 1g of polyethylene glycol and add them to 35g of organic solvent, mix them evenly to obtain a mixed solvent; under the conditions of 65℃ and 1400rpm, take 5g of polyvinyl butyral and slowly add it to the mixed solvent, stir thoroughly to obtain a glue solution;
[0043] S3: Prepare zirconia balls with a ball diameter ratio of Φ5mm:Φ10mm:Φ15mm = 2:4:1; add 1g of polyethyleneimine to 45g of organic solvent, mix well, add 255g of zirconia balls, and ball mill at 235rpm for 10min; add 95g of ceramic powder, and ball mill at 175rpm for 2h; add the above-prepared adhesive solution, and ball mill for 11h to obtain ceramic slurry;
[0044] Step 2: Preparation of ceramic green body
[0045] S1: Take ceramic slurry and perform the first stage of vacuum degassing under the conditions of vacuum degree -0.09MPa and ceramic slurry temperature 40℃, controlling the viscosity of ceramic slurry to 5900cP; increase the vacuum degree and perform the second stage of vacuum degassing under the conditions of vacuum degree -0.1MPa and ceramic slurry temperature 35℃, controlling the viscosity of ceramic slurry to 10000cP, to obtain vacuum degassed ceramic slurry;
[0046] S2: Take the vacuum-degassed ceramic slurry and pass it through a casting machine. Control the front blade height to be 2100μm, the rear blade height to be 2000μm, and the casting conveyor speed to be 0.1m / min. Pass it through the heat preservation section, constant speed section, deceleration section, balancing section, and final drying section in sequence. Each section is 1m long. The temperature of the heat preservation section is set to 34℃, the temperature of the constant speed section is set to 39℃, the temperature of the deceleration section is set to 37℃, the temperature of the balancing section is set to 49℃, and the temperature of the final drying section is set to 64℃. After drying, a ceramic green body is obtained.
[0047] Step 3: Preparation of the film for film arrangement
[0048] Take a ceramic green body, cut it, place it in a glue-removing furnace, heat it to 460℃ at a heating rate of 0.5℃ / min, and hold it at that temperature for 90 minutes to obtain a glue-removing sheet.
[0049] Step 4: Fabrication of high-thickness aluminum nitride ceramic substrate
[0050] Take the film, place it in a sintering furnace, introduce nitrogen gas, and heat it to 1680℃ at a heating rate of 0.5℃ / min. Hold the temperature for 3 hours to obtain a high-thickness ceramic substrate.
[0051] Example 2:
[0052] Step 1: Preparation of ceramic slurry
[0053] S1: Select aluminum nitride powder with D50 = 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, take aluminum nitride coarse powder with D50 = 4μm and aluminum nitride fine powder with D50 = 1μm in a mass ratio of 5:5, mix them evenly, and vacuum dry them at 120℃ for 4h to obtain ceramic powder.
[0054] S2: Take anhydrous ethanol, isopropanol, and ethyl acetate in a mass ratio of 2:2:1, mix them evenly to obtain an organic solvent; take 3g of dibutyl phthalate and 3g of polyethylene glycol and add them to 40g of organic solvent, mix them evenly to obtain a mixed solvent; under the conditions of 70℃ and 1500rpm, take 8g of polyvinyl butyral and slowly add it to the mixed solvent, stir thoroughly to obtain a glue solution;
[0055] S3: Prepare zirconia balls with a ball diameter ratio of Φ5mm:Φ10mm:Φ15mm = 3:5:2; add 2g of polyethyleneimine to 50g of organic solvent, mix well, add 260g of zirconia balls, and ball mill at 240rpm for 15min; add 100g of ceramic powder, and ball mill at 180rpm for 3h; add the above-prepared adhesive solution, and ball mill for 12h to obtain ceramic slurry;
[0056] Step 2: Preparation of ceramic green body
[0057] S1: Take ceramic slurry and perform the first stage of vacuum degassing under the conditions of vacuum degree -0.08MPa and ceramic slurry temperature 43℃, controlling the viscosity of ceramic slurry to 6000cP; increase the vacuum degree and perform the second stage of vacuum degassing under the conditions of vacuum degree -0.095MPa and ceramic slurry temperature 38℃, controlling the viscosity of ceramic slurry to 12000cP, to obtain vacuum degassed ceramic slurry;
[0058] S2: Take the vacuum-degassed ceramic slurry and pass it through a casting machine. Control the front blade height to be 2100μm, the rear blade height to be 2000μm, and the casting conveyor speed to be 0.2m / min. Pass it through the heat preservation section, constant speed section, deceleration section, balancing section, and final drying section in sequence. Each section is 1.5m long. The temperature of the heat preservation section is set to 35℃, the temperature of the constant speed section is set to 40℃, the temperature of the deceleration section is set to 38℃, the temperature of the balancing section is set to 50℃, and the temperature of the final drying section is set to 65℃. After drying, a ceramic green body is obtained.
[0059] Step 3: Preparation of the film for film arrangement
[0060] Take a ceramic green body, cut it, place it in a glue-removing furnace, heat it to 510℃ at a heating rate of 1℃ / min, hold it at the temperature for 105min, and obtain a glue-removing sheet.
[0061] Step 4: Fabrication of high-thickness aluminum nitride ceramic substrate
[0062] Take the film, place it in a sintering furnace, introduce nitrogen gas, and heat it to 1730℃ at a heating rate of 1.5℃ / min. Hold the temperature for 4.5 hours to obtain a high-thickness ceramic substrate.
[0063] Example 3:
[0064] Step 1: Preparation of ceramic slurry
[0065] S1: Select aluminum nitride powder with D50 = 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, take aluminum nitride coarse powder with D50 = 5μm and aluminum nitride fine powder with D50 = 1.5μm at a mass ratio of 7:3, mix them evenly, and vacuum dry them at 125℃ for 5h to obtain ceramic powder;
[0066] S2: Take anhydrous ethanol, isopropanol, and ethyl acetate in a mass ratio of 2.5:2.5:1.5, mix them evenly to obtain an organic solvent; take 5g of dibutyl phthalate and 5g of polyethylene glycol and add them to 45g of organic solvent, mix them evenly to obtain a mixed solvent; under the conditions of 75℃ and 1600rpm, take 10g of polyvinyl butyral and slowly add it to the mixed solvent, stir thoroughly to obtain a glue solution;
[0067] S3: Prepare zirconia balls according to the ball diameter ratio of Φ5mm:Φ10mm:Φ15mm = 4:6:3; add 3g of polyethyleneimine to 55g of organic solvent, mix evenly, add 265g of zirconia balls, and ball mill at 245rpm for 20min; add 105g of ceramic powder, and ball mill at 185rpm for 4h; add the above-prepared adhesive solution, and ball mill for 13h to obtain ceramic slurry;
[0068] Step 2: Preparation of ceramic green body
[0069] S1: Take ceramic slurry and perform the first stage of vacuum degassing under the conditions of vacuum degree -0.07MPa and ceramic slurry temperature 45℃, controlling the viscosity of ceramic slurry to 6100cP; increase the vacuum degree and perform the second stage of vacuum degassing under the conditions of vacuum degree -0.09MPa and ceramic slurry temperature 40℃, controlling the viscosity of ceramic slurry to 14000cP, to obtain vacuum degassed ceramic slurry;
[0070] S2: Take the vacuum-degassed ceramic slurry and pass it through a casting machine. Control the front blade height to be 2100μm, the rear blade height to be 2000μm, and the casting conveyor speed to be 0.3m / min. Pass it through the heat preservation section, constant speed section, deceleration section, balancing section, and final drying section in sequence. Each section is 2m long. The temperature of the heat preservation section is set to 36℃, the temperature of the constant speed section is set to 41℃, the temperature of the deceleration section is set to 39℃, the temperature of the balancing section is set to 51℃, and the temperature of the final drying section is set to 66℃. After drying, a ceramic green body is obtained.
[0071] Step 3: Preparation of the film for film arrangement
[0072] Take a ceramic green body, cut it, place it in a glue-removing furnace, heat it to 560℃ at a heating rate of 1.5℃ / min, hold it at the temperature for 120min, and obtain a glue-removing sheet;
[0073] Step 4: Fabrication of high-thickness aluminum nitride ceramic substrate
[0074] Take the film, place it in a sintering furnace, introduce nitrogen gas, and heat it to 1780℃ at a heating rate of 2.5℃ / min. Hold the temperature for 6 hours to obtain a high-thickness ceramic substrate.
[0075] Example 4:
[0076] Step 1: Preparation of ceramic slurry
[0077] S1: Add 100g of aluminum hydroxide to 500mL of deionized water and mix well to obtain an aluminum hydroxide solution; add 120g of fructose to 300mL of 8% ammonia solution and mix well to obtain a fructose solution; add 155g of urea to the aluminum hydroxide solution and mix well, then add 5g of polyethylene glycol and mix well to obtain a mixed solution; slowly add the mixed solution to the fructose solution and react at 85℃ for 3 hours, then filter, wash, dry, pulverize, and sieve to obtain the precursor powder;
[0078] S2: Take the precursor powder, evacuate, introduce nitrogen gas, react at 1600℃ for 4 hours, and decarburize at 650℃ in air for 3 hours to obtain aluminum nitride powder.
[0079] S3: Select aluminum nitride powder with D50 = 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, take aluminum nitride coarse powder with D50 = 4μm and aluminum nitride fine powder with D50 = 1μm in a mass ratio of 5:5, mix them evenly, and vacuum dry them at 120℃ for 4h to obtain ceramic powder.
[0080] S4: Take anhydrous ethanol, isopropanol, and ethyl acetate in a mass ratio of 2:2:1, mix them evenly to obtain an organic solvent; take 3g of dibutyl phthalate and 3g of polyethylene glycol and add them to 40g of organic solvent, mix them evenly to obtain a mixed solvent; under the conditions of 70℃ and 1500rpm, take 8g of polyvinyl butyral and slowly add it to the mixed solvent, stir thoroughly to obtain a glue solution;
[0081] S5: Prepare zirconia balls according to the ball diameter ratio of Φ5mm:Φ10mm:Φ15mm = 3:5:2; add 1g of polyethyleneimine, 1g of tartaric acid, and 1g of oleic acid to 50g of organic solvent, mix evenly, add 260g of zirconia balls, and ball mill for 15min at 240rpm; add 100g of ceramic powder, 5g of calcium fluoride, and 1g of aluminum powder, and ball mill for 3h at 180rpm; add the above-prepared adhesive solution, and ball mill for 12h to obtain ceramic slurry;
[0082] Step 2: Preparation of ceramic green body
[0083] S1: Take ceramic slurry and perform the first stage of vacuum degassing under the conditions of vacuum degree -0.08MPa and ceramic slurry temperature 43℃, controlling the viscosity of ceramic slurry to 6000cP; increase the vacuum degree and perform the second stage of vacuum degassing under the conditions of vacuum degree -0.095MPa and ceramic slurry temperature 38℃, controlling the viscosity of ceramic slurry to 12000cP, to obtain vacuum degassed ceramic slurry;
[0084] S2: Take the vacuum-degassed ceramic slurry and pass it through a casting machine. Control the front blade height to be 2100μm, the rear blade height to be 2000μm, and the casting conveyor speed to be 0.2m / min. Pass it through the heat preservation section, constant speed section, deceleration section, balancing section, and final drying section in sequence. Each section is 1.5m long. The temperature of the heat preservation section is set to 35℃, the temperature of the constant speed section is set to 40℃, the temperature of the deceleration section is set to 38℃, the temperature of the balancing section is set to 50℃, and the temperature of the final drying section is set to 65℃. After drying, a ceramic green body is obtained.
[0085] Step 3: Preparation of the film for film arrangement
[0086] Take a ceramic green body, cut it, place it in a glue-removing furnace, heat it to 510℃ at a heating rate of 1℃ / min, hold it at the temperature for 105min, and obtain a glue-removing sheet.
[0087] Step 4: Fabrication of high-thickness aluminum nitride ceramic substrate
[0088] Take the film, place it in a sintering furnace, introduce nitrogen gas, and heat it to 1730℃ at a heating rate of 1.5℃ / min. Hold the temperature for 4.5 hours to obtain a high-thickness ceramic substrate.
[0089] Comparative Example 1: The organic solvent was 100% anhydrous ethanol, and the rest were as described in Example 2;
[0090] Step 1: Preparation of ceramic slurry
[0091] S1: Select aluminum nitride powder with D50 = 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, take aluminum nitride coarse powder with D50 = 4μm and aluminum nitride fine powder with D50 = 1μm in a mass ratio of 5:5, mix them evenly, and vacuum dry them at 120℃ for 4h to obtain ceramic powder.
[0092] S2: Take 3g of dibutyl phthalate and 3g of polyethylene glycol and add them to 40g of anhydrous ethanol. Mix them evenly to obtain a mixed solvent. Under the conditions of 70℃ and 1500rpm, take 8g of polyvinyl butyral and slowly add it to the mixed solvent. Stir thoroughly to obtain a glue solution.
[0093] S3: Prepare zirconia balls according to the ball diameter ratio of Φ5mm:Φ10mm:Φ15mm = 3:5:2; add 2g of polyethyleneimine to 50g of anhydrous ethanol, mix evenly, add 260g of zirconia balls, and ball mill for 15min at 240rpm; add 100g of ceramic powder, and ball mill for 3h at 180rpm; add the above-prepared adhesive solution, and ball mill for 12h to obtain ceramic slurry.
[0094] Comparative Example 2: The height of the front blade was adjusted to 1100 μm and the height of the rear blade was adjusted to 1000 μm. Ceramic green bodies were prepared by isostatic pressing and stacking. The rest is the same as in Example 2.
[0095] Step 1: Preparation of ceramic slurry
[0096] S1: Select aluminum nitride powder with D50 = 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, take aluminum nitride coarse powder with D50 = 4μm and aluminum nitride fine powder with D50 = 1μm in a mass ratio of 5:5, mix them evenly, and vacuum dry them at 120℃ for 4h to obtain ceramic powder.
[0097] S2: Take anhydrous ethanol, isopropanol, and ethyl acetate in a mass ratio of 2:2:1, mix them evenly to obtain an organic solvent; take 3g of dibutyl phthalate and 3g of polyethylene glycol and add them to 40g of organic solvent, mix them evenly to obtain a mixed solvent; under the conditions of 70℃ and 1500rpm, take 8g of polyvinyl butyral and slowly add it to the mixed solvent, stir thoroughly to obtain a glue solution;
[0098] S3: Prepare zirconia balls with a ball diameter ratio of Φ5mm:Φ10mm:Φ15mm = 3:5:2; add 2g of polyethyleneimine to 50g of organic solvent, mix well, add 260g of zirconia balls, and ball mill at 240rpm for 15min; add 100g of ceramic powder, and ball mill at 180rpm for 3h; add the above-prepared adhesive solution, and ball mill for 12h to obtain ceramic slurry;
[0099] Step 2: Preparation of ceramic green body
[0100] S1: Take ceramic slurry and perform the first stage of vacuum degassing under the conditions of vacuum degree -0.08MPa and ceramic slurry temperature 43℃, controlling the viscosity of ceramic slurry to 6000cP; increase the vacuum degree and perform the second stage of vacuum degassing under the conditions of vacuum degree -0.095MPa and ceramic slurry temperature 38℃, controlling the viscosity of ceramic slurry to 12000cP, to obtain vacuum degassed ceramic slurry;
[0101] S2: Vacuum-degassed ceramic slurry is passed through a casting machine, with the front blade height controlled at 1100μm, the rear blade height at 1000μm, and the casting conveyor speed at 0.2m / min. The slurry passes through a heat preservation section, a constant speed section, a deceleration section, a balancing section, and a final drying section, each section being 1.5m long. The temperature of the heat preservation section is set to 35℃, the temperature of the constant speed section to 40℃, the temperature of the deceleration section to 38℃, the temperature of the balancing section to 50℃, and the temperature of the final drying section to 65℃ for drying. The slurry is then pressed for 3 minutes at a temperature of 125℃ and a pressure of 14MPa to obtain a ceramic green body.
[0102] Comparative Example 3: Only aluminum nitride coarse powder was added, and the rest were the same as in Example 4;
[0103] Step 1: Preparation of ceramic slurry
[0104] S1: Add 100g of aluminum hydroxide to 500mL of deionized water and mix well to obtain an aluminum hydroxide solution; add 120g of fructose to 300mL of 8% ammonia solution and mix well to obtain a fructose solution; add 155g of urea to the aluminum hydroxide solution and mix well, then add 5g of polyethylene glycol and mix well to obtain a mixed solution; slowly add the mixed solution to the fructose solution and react at 85℃ for 3 hours, then filter, wash, dry, pulverize, and sieve to obtain the precursor powder;
[0105] S2: Take the precursor powder, evacuate, introduce nitrogen gas, react at 1600℃ for 4 hours, and decarburize at 650℃ in air for 3 hours to obtain aluminum nitride powder.
[0106] S3: Select aluminum nitride powder with D50 = 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, take 100g of aluminum nitride coarse powder with D50 = 4μm, and vacuum dry it for 4h at a temperature of 120℃ to obtain ceramic powder.
[0107] Comparative Example 4: Only aluminum nitride fine powder was added; the rest is the same as in Example 4.
[0108] Step 1: Preparation of ceramic slurry
[0109] S1: Add 100g of aluminum hydroxide to 500mL of deionized water and mix well to obtain an aluminum hydroxide solution; add 120g of fructose to 300mL of 8% ammonia solution and mix well to obtain a fructose solution; add 155g of urea to the aluminum hydroxide solution and mix well, then add 5g of polyethylene glycol and mix well to obtain a mixed solution; slowly add the mixed solution to the fructose solution and react at 85℃ for 3 hours, then filter, wash, dry, pulverize, and sieve to obtain the precursor powder;
[0110] S2: Take the precursor powder, evacuate, introduce nitrogen gas, react at 1600℃ for 4 hours, and decarburize at 650℃ in air for 3 hours to obtain aluminum nitride powder.
[0111] S3: Select aluminum nitride powder with D50 = 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, take 100g of aluminum nitride fine powder with D50 = 1μm, and vacuum dry it for 4h at a temperature of 120℃ to obtain ceramic powder.
[0112] Comparative Example 5: No staged vacuum degassing was performed; all other aspects are the same as in Example 4.
[0113] Step 1: Preparation of ceramic slurry
[0114] S1: Add 100g of aluminum hydroxide to 500mL of deionized water and mix well to obtain an aluminum hydroxide solution; add 120g of fructose to 300mL of 8% ammonia solution and mix well to obtain a fructose solution; add 155g of urea to the aluminum hydroxide solution and mix well, then add 5g of polyethylene glycol and mix well to obtain a mixed solution; slowly add the mixed solution to the fructose solution and react at 85℃ for 3 hours, then filter, wash, dry, pulverize, and sieve to obtain the precursor powder;
[0115] S2: Take the precursor powder, evacuate, introduce nitrogen gas, react at 1600℃ for 4 hours, and decarburize at 650℃ in air for 3 hours to obtain aluminum nitride powder.
[0116] S3: Select aluminum nitride powder with D50 = 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, take aluminum nitride coarse powder with D50 = 4μm and aluminum nitride fine powder with D50 = 1μm in a mass ratio of 5:5, mix them evenly, and vacuum dry them at 120℃ for 4h to obtain ceramic powder.
[0117] S4: Take anhydrous ethanol, isopropanol, and ethyl acetate in a mass ratio of 2:2:1, mix them evenly to obtain an organic solvent; take 3g of dibutyl phthalate and 3g of polyethylene glycol and add them to 40g of organic solvent, mix them evenly to obtain a mixed solvent; under the conditions of 70℃ and 1500rpm, take 8g of polyvinyl butyral and slowly add it to the mixed solvent, stir thoroughly to obtain a glue solution;
[0118] S5: Prepare zirconia balls according to the ball diameter ratio of Φ5mm:Φ10mm:Φ15mm = 3:5:2; add 1g of polyethyleneimine, 1g of tartaric acid, and 1g of oleic acid to 50g of organic solvent, mix evenly, add 260g of zirconia balls, and ball mill for 15min at 240rpm; add 100g of ceramic powder, 5g of calcium fluoride, and 1g of aluminum powder, and ball mill for 3h at 180rpm; add the above-prepared adhesive solution, and ball mill for 12h to obtain ceramic slurry;
[0119] Step 2: Preparation of ceramic green body
[0120] S1: Take ceramic slurry and degas it under vacuum conditions of -0.095MPa and 38℃. Control the viscosity of the ceramic slurry to 12000cP to obtain vacuum-degassed ceramic slurry.
[0121] Comparative Example 6: Instead of using the five-stage independent temperature control drying method, constant temperature drying was used, and the rest was the same as in Example 4;
[0122] Step 1: Preparation of ceramic slurry
[0123] S1: Add 100g of aluminum hydroxide to 500mL of deionized water and mix well to obtain an aluminum hydroxide solution; add 120g of fructose to 300mL of 8% ammonia solution and mix well to obtain a fructose solution; add 155g of urea to the aluminum hydroxide solution and mix well, then add 5g of polyethylene glycol and mix well to obtain a mixed solution; slowly add the mixed solution to the fructose solution and react at 85℃ for 3 hours, then filter, wash, dry, pulverize, and sieve to obtain the precursor powder;
[0124] S2: Take the precursor powder, evacuate, introduce nitrogen gas, react at 1600℃ for 4 hours, and decarburize at 650℃ in air for 3 hours to obtain aluminum nitride powder.
[0125] S3: Select aluminum nitride powder with D50 = 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, take aluminum nitride coarse powder with D50 = 4μm and aluminum nitride fine powder with D50 = 1μm in a mass ratio of 5:5, mix them evenly, and vacuum dry them at 120℃ for 4h to obtain ceramic powder.
[0126] S4: Take anhydrous ethanol, isopropanol, and ethyl acetate in a mass ratio of 2:2:1, mix them evenly to obtain an organic solvent; take 3g of dibutyl phthalate and 3g of polyethylene glycol and add them to 40g of organic solvent, mix them evenly to obtain a mixed solvent; under the conditions of 70℃ and 1500rpm, take 8g of polyvinyl butyral and slowly add it to the mixed solvent, stir thoroughly to obtain a glue solution;
[0127] S5: Prepare zirconia balls according to the ball diameter ratio of Φ5mm:Φ10mm:Φ15mm = 3:5:2; add 1g of polyethyleneimine, 1g of tartaric acid, and 1g of oleic acid to 50g of organic solvent, mix evenly, add 260g of zirconia balls, and ball mill for 15min at 240rpm; add 100g of ceramic powder, 5g of calcium fluoride, and 1g of aluminum powder, and ball mill for 3h at 180rpm; add the above-prepared adhesive solution, and ball mill for 12h to obtain ceramic slurry;
[0128] Step 2: Preparation of ceramic green body
[0129] S1: Take ceramic slurry and perform the first stage of vacuum degassing under the conditions of vacuum degree -0.08MPa and ceramic slurry temperature 43℃, controlling the viscosity of ceramic slurry to 6000cP; increase the vacuum degree and perform the second stage of vacuum degassing under the conditions of vacuum degree -0.095MPa and ceramic slurry temperature 38℃, controlling the viscosity of ceramic slurry to 12000cP, to obtain vacuum degassed ceramic slurry;
[0130] S2: Take the vacuum-degassed ceramic slurry and pass it through a casting machine. Control the front blade height to be 2100μm, the rear blade height to be 2000μm, the casting conveying speed to be 0.2m / min, and the drying temperature to be 46℃. Dry the slurry to obtain a ceramic green body.
[0131] Comparative Example 7: Tartaric acid was not added; otherwise, refer to Example 4.
[0132] Step 1: Preparation of ceramic slurry
[0133] S1: Add 100g of aluminum hydroxide to 500mL of deionized water and mix well to obtain an aluminum hydroxide solution; add 120g of fructose to 300mL of 8% ammonia solution and mix well to obtain a fructose solution; add 155g of urea to the aluminum hydroxide solution and mix well, then add 5g of polyethylene glycol and mix well to obtain a mixed solution; slowly add the mixed solution to the fructose solution and react at 85℃ for 3 hours, then filter, wash, dry, pulverize, and sieve to obtain the precursor powder;
[0134] S2: Take the precursor powder, evacuate, introduce nitrogen gas, react at 1600℃ for 4 hours, and decarburize at 650℃ in air for 3 hours to obtain aluminum nitride powder.
[0135] S3: Select aluminum nitride powder with D50 = 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, take aluminum nitride coarse powder with D50 = 4μm and aluminum nitride fine powder with D50 = 1μm in a mass ratio of 5:5, mix them evenly, and vacuum dry them at 120℃ for 4h to obtain ceramic powder.
[0136] S4: Take anhydrous ethanol, isopropanol, and ethyl acetate in a mass ratio of 2:2:1, mix them evenly to obtain an organic solvent; take 3g of dibutyl phthalate and 3g of polyethylene glycol and add them to 40g of organic solvent, mix them evenly to obtain a mixed solvent; under the conditions of 70℃ and 1500rpm, take 8g of polyvinyl butyral and slowly add it to the mixed solvent, stir thoroughly to obtain a glue solution;
[0137] S5: Prepare zirconia balls according to the ball diameter ratio of Φ5mm:Φ10mm:Φ15mm = 3:5:2; add 1g of polyethyleneimine and 1g of oleic acid to 50g of organic solvent, mix evenly, add 260g of zirconia balls, and ball mill for 15min at 240rpm; add 100g of ceramic powder, 5g of calcium fluoride and 1g of aluminum powder, and ball mill for 3h at 180rpm; add the above-prepared adhesive solution, and ball mill for 12h to obtain ceramic slurry.
[0138] Comparative Example 8: No aluminum powder was added; otherwise, refer to Example 4.
[0139] Step 1: Preparation of ceramic slurry
[0140] S1: Add 100g of aluminum hydroxide to 500mL of deionized water and mix well to obtain an aluminum hydroxide solution; add 120g of fructose to 300mL of 8% ammonia solution and mix well to obtain a fructose solution; add 155g of urea to the aluminum hydroxide solution and mix well, then add 5g of polyethylene glycol and mix well to obtain a mixed solution; slowly add the mixed solution to the fructose solution and react at 85℃ for 3 hours, then filter, wash, dry, pulverize, and sieve to obtain the precursor powder;
[0141] S2: Take the precursor powder, evacuate, introduce nitrogen gas, react at 1600℃ for 4 hours, and decarburize at 650℃ in air for 3 hours to obtain aluminum nitride powder.
[0142] S3: Select aluminum nitride powder with D50 = 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, take aluminum nitride coarse powder with D50 = 4μm and aluminum nitride fine powder with D50 = 1μm in a mass ratio of 5:5, mix them evenly, and vacuum dry them at 120℃ for 4h to obtain ceramic powder.
[0143] S4: Take anhydrous ethanol, isopropanol, and ethyl acetate in a mass ratio of 2:2:1, mix them evenly to obtain an organic solvent; take 3g of dibutyl phthalate and 3g of polyethylene glycol and add them to 40g of organic solvent, mix them evenly to obtain a mixed solvent; under the conditions of 70℃ and 1500rpm, take 8g of polyvinyl butyral and slowly add it to the mixed solvent, stir thoroughly to obtain a glue solution;
[0144] S5: Prepare zirconia balls according to the ball diameter ratio of Φ5mm:Φ10mm:Φ15mm = 3:5:2; add 1g of polyethyleneimine, 1g of tartaric acid and 1g of oleic acid to 50g of organic solvent, mix evenly, add 260g of zirconia balls, and ball mill for 15min at 240rpm; add 100g of ceramic powder and 5g of calcium fluoride, and ball mill for 3h at 180rpm; add the above-prepared adhesive solution, and ball mill for 12h to obtain ceramic slurry.
[0145] Comparative Example 9: No oleic acid was added; otherwise, refer to Example 4.
[0146] Step 1: Preparation of ceramic slurry
[0147] S1: Add 100g of aluminum hydroxide to 500mL of deionized water and mix well to obtain an aluminum hydroxide solution; add 120g of fructose to 300mL of 8% ammonia solution and mix well to obtain a fructose solution; add 155g of urea to the aluminum hydroxide solution and mix well, then add 5g of polyethylene glycol and mix well to obtain a mixed solution; slowly add the mixed solution to the fructose solution and react at 85℃ for 3 hours, then filter, wash, dry, pulverize, and sieve to obtain the precursor powder;
[0148] S2: Take the precursor powder, evacuate, introduce nitrogen gas, react at 1600℃ for 4 hours, and decarburize at 650℃ in air for 3 hours to obtain aluminum nitride powder.
[0149] S3: Select aluminum nitride powder with D50 = 0.5-5μm, sieve aluminum nitride powder with different D50 particle sizes, take aluminum nitride coarse powder with D50 = 4μm and aluminum nitride fine powder with D50 = 1μm in a mass ratio of 5:5, mix them evenly, and vacuum dry them at 120℃ for 4h to obtain ceramic powder.
[0150] S4: Take anhydrous ethanol, isopropanol, and ethyl acetate in a mass ratio of 2:2:1, mix them evenly to obtain an organic solvent; take 3g of dibutyl phthalate and 3g of polyethylene glycol and add them to 40g of organic solvent, mix them evenly to obtain a mixed solvent; under the conditions of 70℃ and 1500rpm, take 8g of polyvinyl butyral and slowly add it to the mixed solvent, stir thoroughly to obtain a glue solution;
[0151] S5: Prepare zirconia balls according to the ball diameter ratio of Φ5mm:Φ10mm:Φ15mm = 3:5:2; add 1g of polyethyleneimine and 1g of tartaric acid to 50g of organic solvent, mix evenly, add 260g of zirconia balls, and ball mill for 15min at 240rpm; add 100g of ceramic powder, 5g of calcium fluoride and 1g of aluminum powder, and ball mill for 3h at 180rpm; add the above-prepared adhesive solution, and ball mill for 12h to obtain ceramic slurry.
[0152] experiment:
[0153] The properties of the high-thickness ceramic substrates prepared in Examples 1-4 and Comparative Examples 1-9 were measured.
[0154] (1) Thermal property determination
[0155] The thermal diffusivity of a thick ceramic substrate was determined using an LFA447 laser thermal conductivity meter. The sample size was 10 mm × 10 mm × 2 mm. Three replicates were performed, and the average value was taken. The specific heat capacity was taken as 0.734 J·g. -1 ·K -1 Calculate the thermal conductivity;
[0156] (2) Mechanical property determination
[0157] The bending strength of a high-thickness ceramic substrate was determined by the three-point bending method. The sample size was 3mm×4mm×36mm. Six sets were repeated and the average value was taken.
[0158] The data obtained from the above experiment are shown in Table 1 below:
[0159] Table 1
[0160]
[0161]
[0162] Conclusion: Based on the analysis of the above experimental data, the high-thickness ceramic substrates prepared in Examples 1-4 of this invention have higher thermal conductivity and bending strength, excellent thermal and mechanical properties, good thermal conductivity, and longer service life; while the high-thickness ceramic substrates prepared in Comparative Examples 1-9 have lower thermal conductivity and bending strength, poorer thermal and mechanical properties, poor thermal conductivity, and shorter service life.
[0163] Comparative analysis of Comparative Example 1 and Example 2, where the organic solvent is 100% anhydrous ethanol, shows that compared to a single solvent system, the use of anhydrous ethanol, isopropanol, and ethyl acetate as organic solvents, and anhydrous ethanol and isopropanol as polar solvents, allows hydroxyl groups to react with polar groups on the powder surface to form hydrogen bonds, enhancing powder wettability, improving dispersibility, and inhibiting particle agglomeration. Ethyl acetate, as a high-boiling-point solvent, regulates the evaporation rate and prevents cracking during the drying of high-thickness aluminum nitride green blanks.
[0164] By adjusting the height of the front blade to 1100 μm and the height of the rear blade to 1000 μm, a comparative analysis of Comparative Example 2 and Example 2, which uses isostatic pressing to prepare ceramic green bodies, shows that the isostatic pressing method is not only cumbersome, but also results in high-thickness aluminum nitride green bodies that are prone to defects at the interface during sintering, leading to poor sintering performance.
[0165] Comparative analysis of Comparative Example 3 (which only added coarse aluminum nitride powder) and Example 4 shows that by graded and proportioned aluminum nitride powder according to particle size, aluminum nitride powder with a D50 particle size of 0.5-5μm is selected, and aluminum nitride powder with different D50 particle sizes is sieved. Coarse aluminum nitride powder with D50 = 3-5μm and fine aluminum nitride powder with D50 = 0.5-1.5μm are taken at a mass ratio of (3-7): (3-7) and mixed evenly to obtain ceramic powder. Among them, by mixing coarse aluminum nitride powder and fine aluminum nitride powder with different particle sizes, a gradation effect is achieved, and the pores between large particles are filled with small particles. This avoids the problem of excessively large pores between particles when only coarse aluminum nitride powder is added. This further controls the stability, fluidity and solid content of the ceramic slurry, which is beneficial for preparing ceramic substrates with high thickness, high density, high thermal conductivity and high mechanical properties.
[0166] Comparative analysis of Comparative Example 4 (which only added fine aluminum nitride powder) and Example 4 shows that, according to the particle size of the aluminum nitride powder, aluminum nitride powder with a D50 particle size of 0.5-5μm was selected, and aluminum nitride powder with different D50 particle sizes was sieved. At a mass ratio of (3-7):(3-7), coarse aluminum nitride powder with D50=3-5μm and fine aluminum nitride powder with D50=0.5-1.5μm were taken and mixed evenly to obtain ceramic powder. Among them, by mixing coarse aluminum nitride powder and fine aluminum nitride powder with different particle sizes, a gradation effect is achieved, and the pores between large particles are filled with small particles, avoiding particle agglomeration when only fine aluminum nitride powder is added. This further controls the stability, fluidity and solid content of the ceramic slurry, which is beneficial for preparing ceramic substrates with high thickness, high density, high thermal conductivity and high mechanical properties.
[0167] Comparative analysis of Comparative Example 5 (without staged vacuum degassing) and Example 4 shows that staged vacuum degassing involves two main stages. In the first stage, vacuum degassing is performed at a vacuum level of -0.09 to -0.08 MPa and a ceramic slurry temperature of 40-45°C, controlling the ceramic slurry viscosity to 6000-8000 cP. During this stage, a large amount of solvent is removed, increasing the slurry viscosity and solid content, primarily removing large air bubbles from the lower viscosity slurry. In the second stage, vacuum degassing is performed at a vacuum level of -0.095 to -0.09 MPa and a ceramic slurry temperature of 35-40°C, controlling the ceramic slurry viscosity to 10000-14000 cP. This stage primarily removes tiny air bubbles from the high viscosity slurry. By coordinating these two stages of vacuum degassing, air bubbles in the slurry are eliminated to the maximum extent, which is beneficial for improving the thermal and mechanical properties of the ceramic substrate.
[0168] Comparative analysis of Comparative Example 6 and Example 4, which replaced the five-stage independent temperature-controlled drying with constant-temperature drying, shows that the five-stage independent temperature-controlled drying process sequentially passes through a heat preservation stage, a constant-speed stage, a falling-speed stage, a balancing stage, and a final drying stage. The heat preservation stage temperature is set at 34-36℃ to maintain slurry stability, promote the removal of low-boiling-point alcohol solvents, and form porous surface channels to provide pathways for subsequent solvent migration. The constant-speed stage temperature is set at 39-41℃, allowing the main solvent to migrate from the porous surface channels to the surface through capillary action, promoting the removal of the main solvent. The falling-speed stage temperature is set at 3... The drying process is carried out at 7-39℃ to reduce the drying rate, thereby reducing the solvent removal rate, releasing internal stress, and preventing cracking of the aluminum nitride green body. The equilibrium section temperature is set at 49-51℃ to promote the diffusion of solvent from the high water content area to the low water content area through the temperature gradient, which dominates migration and promotes the removal of residual solvent. The final drying section temperature is set at 64-66℃ to completely remove the solvent. The hot air circulation system is then turned on to prevent condensation backflow. The drying process balances the drying rate and the casting rate, avoiding both excessively fast drying, which inhibits cracking of the green body, and excessively slow drying, which affects the green body forming. This is beneficial to improving the thermal and mechanical properties of the ceramic substrate.
[0169] Comparative analysis of Comparative Example 7 (without tartaric acid) and Example 4 shows that, with the addition of tartaric acid, on the one hand, the hydroxyl and carboxyl groups of tartaric acid chemically bond with the hydroxyl groups on the surface of aluminum nitride powder, forming a coating layer on the surface of aluminum nitride powder, which inhibits particle agglomeration through steric hindrance; on the other hand, the carboxyl groups of tartaric acid ionize to form carboxylate ions, which adsorb on the surface of aluminum nitride powder, inhibiting particle agglomeration through electrostatic interaction.
[0170] Polyethyleneimine is used as a dispersant. The molecular chain of polyethyleneimine is positively charged, which easily causes bridging flocculation. Tartaric acid is added. Tartaric acid is negatively charged, which neutralizes the positive charge of the polyethyleneimine molecular chain and avoids flocculation. The synergistic effect of the two improves the dispersibility of aluminum nitride powder, which is beneficial for preparing ceramic slurries with high solid content, further preparing high-thickness aluminum nitride green bodies, and making it easier to prepare ceramic substrates with high thickness, high density, high thermal conductivity and high mechanical properties.
[0171] Comparative analysis of Comparative Example 8 (without aluminum powder) and Example 4 shows that aluminum powder, as an aluminum source, reacts with nitrogen to form aluminum nitride nuclei, which strengthens grain boundaries, purifies the aluminum nitride lattice, and refines the second phase, thus improving the thermal and mechanical properties of the ceramic substrate.
[0172] Comparative analysis of Comparative Example 9 (without oleic acid) and Example 4 shows that oleic acid is selected as a surface modifier for ceramic powder. Oleic acid has a hydrophilic carboxyl group and a hydrophobic alkyl long chain. The hydrophilic carboxyl group and the hydroxyl group or uncoordinated aluminum ions on the surface of aluminum nitride are chemically bonded to form a coating layer on the surface of aluminum nitride, which improves dispersibility and hydrolysis resistance, and is beneficial to improving the thermal and mechanical properties of ceramic substrates.
[0173] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A method for preparing and molding a high-thickness aluminum nitride green billet, characterized in that: Includes the following steps: Step 1: Take aluminum nitride powder, sieve it to obtain coarse aluminum nitride powder and fine aluminum nitride powder; take coarse aluminum nitride powder and fine aluminum nitride powder, mix them evenly, and vacuum dry them to obtain ceramic powder; Step 2: Add dispersant and surface modifier to organic solvent, mix well, add zirconia balls, and ball mill; add ceramic powder and sintering aid, ball mill; add adhesive, ball mill, to obtain ceramic slurry; Step 3: Take the ceramic slurry, degas it under vacuum to obtain a vacuum-degassed ceramic slurry; Step 4: Take the vacuum-degassed ceramic slurry, pass it through a casting machine, cast it, and dry it to obtain a ceramic green body; Step 5: Take the ceramic green body, cut it, remove the glue, and obtain a glue-removing sheet; take the glue-removing sheet, introduce nitrogen gas, and sinter to obtain a high-thickness ceramic substrate; The method for preparing the vacuum degassing ceramic slurry is as follows: take the ceramic slurry, and perform the first stage of vacuum degassing under the conditions of vacuum degree (-0.09)-(-0.07) MPa and ceramic slurry temperature 40-45℃, and control the viscosity of the ceramic slurry to 5900-6100 cP. Increase the vacuum level, and carry out the second stage of vacuum degassing under the conditions of vacuum level (-0.1)-(-0.09) MPa and ceramic slurry temperature 35-40℃, control the ceramic slurry viscosity to 10000-14000 cP, and obtain vacuum degassed ceramic slurry. The aluminum nitride powder has a D50 of 0.5-5 μm; the coarse aluminum nitride powder has a D50 of 3-5 μm; the fine aluminum nitride powder has a D50 of 0.5-1.5 μm; and the mass ratio of the coarse aluminum nitride powder to the fine aluminum nitride powder is (3-7):(3-7). The method for preparing the aluminum nitride powder is as follows: aluminum hydroxide is added to deionized water and mixed evenly to obtain an aluminum hydroxide solution; fructose is added to an ammonia solution and mixed evenly to obtain a fructose solution; urea is added to the aluminum hydroxide solution and mixed evenly; polyethylene glycol is added and mixed evenly to obtain a mixed solution; the mixed solution is slowly added to the fructose solution, and the reaction is carried out at a temperature of 80-90℃ for 2-4 hours; the mixture is then filtered, washed, dried, pulverized, and sieved to obtain a precursor powder; the precursor powder is then vacuumed, nitrogen gas is introduced, and the reaction is carried out at a temperature of 1550-1650℃ for 3-5 hours; and then decarburized at a temperature of 600-700℃ in an air atmosphere for 2-4 hours to obtain aluminum nitride powder. The dispersant is polyethyleneimine and tartaric acid.
2. The method for preparing and forming a high-thickness aluminum nitride green billet according to claim 1, characterized in that: The preparation method of the adhesive solution is as follows: plasticizer and polyethylene glycol are added to an organic solvent and mixed evenly to obtain a mixed solvent; under the conditions of temperature 65-75℃ and rotation speed 1400-1600rpm, adhesive is slowly added to the mixed solvent and stirred thoroughly to obtain the adhesive solution.
3. The method for preparing and forming a high-thickness aluminum nitride green billet according to claim 2, characterized in that: The plasticizer is one of dibutyl phthalate, triethyl citrate, and acetylated tributyl citrate; the binder is one of polyvinyl butyral and ethyl cellulose.
4. The method for preparing and forming a high-thickness aluminum nitride green billet according to claim 1, characterized in that: The method for preparing the ceramic green body is as follows: vacuum degassing ceramic slurry is passed through a casting machine, the height of the scraper is controlled to be 2-2.2 mm, the casting conveying speed is controlled to be 0.1-0.3 m / min, and the slurry passes through the heat preservation section, constant speed section, deceleration section, balance section and final drying section in sequence, each section being 1-2 m long, and then dried to obtain the ceramic green body.
5. The method for preparing and forming a high-thickness aluminum nitride green billet according to claim 4, characterized in that: The temperature of the heat preservation section is set to 34-36℃; the temperature of the constant speed section is set to 39-41℃; the temperature of the deceleration section is set to 37-39℃; the temperature of the balancing section is set to 49-51℃; and the temperature of the final drying section is set to 64-66℃.
6. The method for preparing and forming a high-thickness aluminum nitride green billet according to claim 1, characterized in that: The surface modifier is one of oleic acid and stearic acid; the organic solvent is one or more of methanol, anhydrous ethanol, isopropanol, ethyl acetate, and propyl acetate; the sintering aid is one or more of calcium fluoride and metallic aluminum powder; the diameter ratio of the zirconia balls is: Φ5mm:Φ10mm:Φ15mm=(2-4):(4-6):(1-3).
7. The method for preparing and forming a high-thickness aluminum nitride green billet according to claim 1, characterized in that: In step five, the debinding process is as follows: under the condition of heating rate of 0.5-1.5℃ / min, the temperature is raised to 460-560℃ and held for 90-120 minutes; the sintering process is as follows: under the condition of heating rate of 0.5-2.5℃ / min, the temperature is raised to 1680-1780℃ and held for 3-6 hours.
Citation Information
Patent Citations
Tape casting aluminum nitride green body manufacturing method
CN103121238A
Method for preparing AlN raw ceramic chip for multi-layer wiring substrate by virtue of tape casting process and prepared AlN ceramic chip
CN104193340A
Method for preparing nanometer AlN powder through hydrothermal method and intermediate and product produced through method
CN106431418A
Slurry of high-performance aluminum nitride ceramic substrate and preparation method thereof
CN112374896A
Pole piece and preparation method thereof, button cell and application
CN117766673A